+0  
 
0
334
1
avatar

Hi!,

 

2^x-2^{x-1}=4

 

I lose the x if i use my 'normal method of immediately 4=2^2 and bringing everything down.

x-(x-1)=2

Guest Sep 8, 2017
 #1
avatar+71 
+1

\(2^{x}-2^{x-1} =4 \)now factor out  to get

 

\(2^{x-1} (2^{1}- 1)=4\)

 

 

\(2^{x-1}(1) =4\)

\(2^{x-1}=4 \)  since we know that \(2^{2}=4\)

 

then x-1  =2    so x =3.

 

Check  2^3   - 2^2    =   8 - 4     =4

frasinscotland  Sep 8, 2017

12 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.